OPTIMIZATION OF THE PREPARATION PROCESS IN MINIBASCHETBALL BY OPERATIONAL STRUCTURES OF COORDINATIVE TYPE - CĂTĂNESCU A.; TOMELE S. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Object of research. Consist in improving the training process of mini basketball players, by introducing some structures of coordinative type, focused on: ball control when passing, reaction times, unipodale and bipodale coordination, balance, court orientation and the ambidextrous. Hypothesis. If in the learning stage of basketball, we will use operational structures of coordinative type, which implies most of the components of the coordinative capacity: (single podal coordination and bi-podal coordination, balance, ball control, field orientation, ambidextrousness), then the speed of assimilation of the technical procedures will increase significantly. Material and methods. Studying the specialty literature, direct and indirect observation, testing methods, mathematical and tabular statistics. Results. By comparing the results gain by at the final evaluation, by the control group and by the experimental group it was observed significant statistic differences (p<0.001) between the two groups, for all the evaluation test realized. These results allowed us to reject the null hypothesis and sustain that preparation programs used by us have improved the performance of the subjects in the experimental group. Conclusions. . So after the results of the proposed experiment and submitting the control samples at all realized tests, the subjects of the experimental group got better results, differences between the evaluations being confirmed statistically. Also, the evaluation tests proposed are described by a progressive growth of the number of elements proposed and tested, but also by the growth of the interaction between the components of coordinative capacity and technical tactic elements specific to basketball.